(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Triazole ring system has attracted a continuously growing interest of synthetic organic chemists and those dealing with the medicinal compounds due to its versatile potential to interact with biological systems. The triazole compounds possess a wide range of biological activities and are especially focused for antifungal behavior. In this review article, we have summarized the recent developments in the synthetic methodologies of this ring system. Enough literature is available demonstrating antibacterial, antifungal, anticonvulsant, antiviral, antidiabetic and antimalarial potential. Owing to their wide application, scientists across the globe are engaged in the design and development of 1,2,3-triazole based medicinal agents.However, the approach for development of such agents involving Huisgen’s cycloaddition reaction has gained immense importance. This manuscript covers different conventional and nonconventional approaches adopted for the synthesis of 1,2,3-triazole derivatives. The main focus was on the methodologies which deal with the facile and convenient synthesis.